Safety and efficacy of a feed additive consisting of a dry extract obtained from the leaves of Ginkgo biloba L. (ginkgo extract) for horses, dogs, cats, rabbits and guinea pigs (FEFANA asbl) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Mojca Durjava; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; Alena Pechová; et al. (EFSA Journal, 2024)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety and efficacy of a feed additive obtained from the dried leaves of Ginkgo biloba L. (ginkgo extract) when used as a sensory additive in feed for horses, dogs, cats, rabbits and guinea pigs. Ginkgo extract contains ≥ 24% total flavonoids, ≥ 6% total terpene lactones and ≤ 1 mg/kg ginkgolic acids. The EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) concluded that ginkgo extract is safe for the target species at the following concentrations in complete feed: 2.8 mg/kg for horses and cats, 1.1 mg/kg for rabbits and guinea pigs, and 3.3 mg/kg for dogs. No safety concern would arise for the consumers from the use of ginkgo extract up to the highest level in feed which is considered safe for food‐producing species (horses and rabbits). The additive should be considered as irritant to skin and eyes, and as a dermal and respiratory sensitiser. The use of the additive at the proposed level in feed for the target species is not considered to be a risk to the environment. While the available data indicate that Ginkgo preparations have a distinctive flavour profile, there is no evidence that the ginkgo extract would impart flavour to a food or feed matrix. Therefore, the FEEDAP Panel cannot conclude on the efficacy of the additive.